Priorities for the transformation of customs and tariff policy in the context of sanctions pressure - A. Belyaev; V. Molodykh (Вестник Северо-Кавказского федерального университета)
Economic sanctions are a broad set of measures to achieve political or economic goals. The sanctions imposed against Russia are multilateral and selective, as they target several critical sectors, such as energy and manufacturing, and are also supported by restrictions on personal travel for individual Russian citizens. Russian counter-sanctions are imposed unilaterally and are selective in nature, affect only a few branches of agriculture and the food industry and are mandatory.   The purpose of the study is to measure the dynamics of Russian exports, and then assess whether the optimal trajectory of foreign trade has been disrupted or not.   The negative impact is measured by the reduction in exports after the imposition of sanctions using a statistical approach based on the description of scenarios. The effect of the deviation of foreign trade is estimated by estimating the difference in gravitational models of foreign trade. Empirical results show that exports to Russia in the sanctioned commodity groups, as well as in the control group, decreased after the introduction of sanctions, but the growth of foreign trade within the EAEU compensated for these losses almost completely. the use of selective instruments of a restrictive customs and tariff policy is more effective and can be used as instruments of trade wars. If we take into account that one of the most important characteristics of effective sanctions is the ability to cause damage to an object, these sanctions cannot be considered as successful in relation to the stated goals. However, since the application of economic sanctions is only intensifying in international politics, it is necessary to develop a set of measures to minimize the damage from their introduction, primarily by diversifying the commodity and territorial structure of exports.